1987
DOI: 10.1093/infdis/155.3.445
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of the Clinical Diagnosis and Course of Lassa Fever

Abstract: A prospective case-control study of Lassa fever was established in Sierra Leone to measure the frequency and case-fatality ratio of Lassa fever among febrile hospital admissions and to better delineate the clinical diagnosis and course of this disease. Lassa fever was responsible for 10%-16% of all adult medical admissions and for approximately 30% of adult deaths in the two hospitals studied. The case-fatality ratio for 441 hospitalized patients was 16.5%. We found the best predictor of Lassa fever to be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
289
6
6

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(313 citation statements)
references
References 13 publications
6
289
6
6
Order By: Relevance
“…[12] In this study records that have to do with the most useful clinical predictors of LF are fever, pharyngitis, retrosternal pain, and proteinuria for diagnosis; and fever, sore throat, and vomiting for outcome were not recorded as part of routine data of patients. [6] A case fatality rate of 52.2% was observed in this study as against a declining rate observed in a previous study conducted in health facilities from 70% -18.5% in 2012-2014. [12] It appears to be higher than the values suggested by CDC that approximately 15%-20% of patients hospitalized for Lassa fever die from the illness.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…[12] In this study records that have to do with the most useful clinical predictors of LF are fever, pharyngitis, retrosternal pain, and proteinuria for diagnosis; and fever, sore throat, and vomiting for outcome were not recorded as part of routine data of patients. [6] A case fatality rate of 52.2% was observed in this study as against a declining rate observed in a previous study conducted in health facilities from 70% -18.5% in 2012-2014. [12] It appears to be higher than the values suggested by CDC that approximately 15%-20% of patients hospitalized for Lassa fever die from the illness.…”
Section: Discussionsupporting
confidence: 44%
“…Although LF presents like malaria, the most useful clinical predictors are fever, pharyngitis, retrosternal pain, and proteinuria for diagnosis; and fever, sore throat, and vomiting for outcome. [6] By June 2017, a total of 501 cases including 104 deaths have been reported since the onset of the current LF outbreaks season in December 2016 in Nigeria. Of the reported cases, 189 have been further classified, 175 laboratory-confirmed including 59 deaths and 14 probable cases (all dead).…”
Section: Introductionmentioning
confidence: 99%
“…2 Guinea pigs infected with this adapted PIC virus develop fever, leukopenia, thrombocytopenia, platelet dysfunction, 3 and terminal vascular collapse 4 in the absence of significant hemorrhagic manifestations, resembling Lassa fever. 5 Like Lassa virus in humans, adapted PIC virus replicates in all extraneural tissues of guinea pigs, and induces minimal histopathologic changes in liver, spleen and other reticuloendothelial organs of the infected host. [6][7][8] In contrast, the parental, unpassaged virus is naturally attenuated, and causes a self-limited febrile illness with low mortality in inbred guinea pigs.…”
mentioning
confidence: 99%
“…We did not model outbreaks due to the Lassa arenavirus, because few epidemiologic data are available and a different model, which addresses zoonotic transmission of this agent, would be essential, but the benefits of early diagnosis could be greater for Lassa fever-endemic areas in West Africa. There, Lassa fever infects many more people than all filoviruses combined and accounts for a considerable number of hospitalizations -up to 15% in highly endemic areas [46,47] -and early treatment with the antiviral ribavarin significantly improves prognosis [48]. As ribavarin is costly, any diagnostic protocol that delineates presumptive Lassa fever cases from malaria will help to target its use.…”
Section: Discussionmentioning
confidence: 99%